Avidity of antineurocytoskeletal antibodies in Alzheimer's disease patients - Noskova, Libuse; Fialova, Lenka; Bartos, Ales; Zima, Tomas (Biomedical papers, 2017)
Aims: To optimise the ELISA method for the avidity of IgG antibodies against neurofilament heavy chain (NfH) and to determine the levels and avidity of anti-NfH antibodies in patients with Alzheimer's disease (AD) and a healthy control group. Methods: Various dilutions of sera and concentrations of urea and sodium chloride as chaotropic reagents were tested in the process of the ELISA optimisation. The levels and avidity of anti-NfH antibodies were determined in 30 patients with Alzheimer's disease and 30 age-matched cognitively normal elderly adults. Results: Sera dilution 1:200 and urea as a chaotrope in a concentration 6 mol/L were chosen to be the most suitable for the avidity assay of anti-NfH antibodies by ELISA. The results showed no differences in either level or avidity of IgG anti-NfH antibodies between AD patients and cognitively normal persons. The levels of anti-NfH IgG antibodies inversely correlated with their avidities. Conclusions: We optimised the ELISA method for the determination of anti-NfH antibody avidity determination which is suitable for research of anti-NfH antibody avidity in patients with neurological diseases associated with neurocytoskeletal defects. The determination of serum anti-NfH antibody avidity in AD patients seems to have limited diagnostic significance.
Keywords: Alzheimer's disease; antibodies; avidity; heavy chain of neurofilament; neurofilament